Essential mathematics for economics and business - Bradley, Teresa; Patton, Paul. (Chichester, West Sussex, England ; New York, NY : John Wiley and Sons, 1998)
This book is about: Mathematical preliminaries; The straight line and applications; Simultaneous equations; Non-linear functions and applications; Financial mathematics; ...
Keywords: Algebra; Business mathematics; Algebra; Business mathematics